1997
DOI: 10.1074/jbc.272.9.5371
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the Low Molecular Weight Phosphotyrosine Phosphatase by Phosphorylation at Tyrosines 131 and 132

Abstract: Activation of resting T lymphocytes is initiated by rapid but transient tyrosine phosphorylation of a number of cellular proteins. Several protein tyrosine kinases and protein tyrosine phosphatases are known to be important for this response. Here we report that normal T lymphocytes express the B isoform of low molecular weight protein tyrosine phosphatase B (LMPTP-B). The cDNA was cloned from Jurkat T cells, and an antiserum was raised against it. LMPTP immunoprecipitated from resting Jurkat T cells was found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
91
1
4

Year Published

1999
1999
2011
2011

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 98 publications
(99 citation statements)
references
References 23 publications
3
91
1
4
Order By: Relevance
“…2F and data not shown). Inactive PTP mutants are often used to study their regulation by phosphorylation on tyrosine residues, because PTPs often show a strong tendency toward auto-dephosphorylation (34,36). Indeed, we observed that TCR-induced phosphorylation of transfected inactive C227S mutants of LYP and PEP was severalfold more prominent than that of the wild type phosphatases (data not shown).…”
Section: Binding Of Csk To Lyp Does Not Directlymentioning
confidence: 58%
See 1 more Smart Citation
“…2F and data not shown). Inactive PTP mutants are often used to study their regulation by phosphorylation on tyrosine residues, because PTPs often show a strong tendency toward auto-dephosphorylation (34,36). Indeed, we observed that TCR-induced phosphorylation of transfected inactive C227S mutants of LYP and PEP was severalfold more prominent than that of the wild type phosphatases (data not shown).…”
Section: Binding Of Csk To Lyp Does Not Directlymentioning
confidence: 58%
“…Given that LYP forms a complex with Csk, a PTK, and the polymorphism affects the PTP/PTK interaction, we considered the possibility that the phosphatase could be phosphorylated on tyrosine. Several PTPs are regulated by tyrosine phosphorylation (34,35), including PTP20 (36), which is homolog to LYP. We found that treatment of human JTAg cells (24) with pervanadate, a powerful PTP inhibitor, induced phosphorylation of LYP on tyrosine ( Fig.…”
Section: Binding Of Csk To Lyp Does Not Directlymentioning
confidence: 99%
“…Thiophosphates, resistant to enzymatic hydrolysis, have been introduced into signaling proteins by enzymatic modification of recombinant proteins with ATP␥S. These are often sluggish reactions that generally afford low stoichiometries and often show poor regioselectivity (33). Moreover, thiophosphates can indeed be hydrolyzed chemically and enzymatically, by some phosphatases almost as rapidly as phosphate substrates (34), in contrast to the nonhydrolyzable analogues used here.…”
Section: Discussionmentioning
confidence: 99%
“…These two LMW-PTP pools are differentially regulated because only the cytoskeleton-associated LMW-PTP fraction is specifically phosphorylated by c-Src after PDGF stimulation (6). As a consequence of its phosphorylation, LMW-PTP shows an average 20-fold increase in its in vitro catalytic activity (7,8,9). Cytoskeleton-associated LMW-PTP influences cell adhesion, spreading, and migration, controlling the phosphorylation level of p190Rho-GAP, a protein that is able to regulate Rho activity and, consequently, cytoskeleton rearrangement in response to PDGF stimulation.…”
mentioning
confidence: 99%